Konferencija u Wannseeu i izazovi memorijalizacije / Wannsee Conference and Memorialization Challenges - Muftić, Lamija (Pregled: časopis za društvena pitanja / Periodical for social issues, 2024)
The Holocaust permanently changed the European continent, and its end and the passing of time bring with it the challenges of remembering and building a society based on different values from those that produced mass crimes and resulted in millions of murdered Jews, Roma, and other social groups that National Socialism recognized as undesirable. The challenge of memory is related primarily to its content, but also to the way it materializes in physical space. With its history, Villa Wannsee illustrates the complex relationship of German society to the legacy of the Holocaust and the long road to recognition of the extent of its damage. From the meeting place of Nazi officials for the administrative organization of the implementation of the Holocaust, through the youth center, to the memorial center, Villa Wannsee bears witness to the initial unwillingness of German society to face Nazi crimes and the gradual development of a culture of remembrance and social education about all the dangers of a state guided by the ideas of the supremacy of one group. whether racial, national or based on other discriminatory grounds.